High-dose vitamin C on sepsis: Protocol of a prospective, multi-centered, double-blinded, randomized, and placebo-controlled superiority study - Zhao, Bing; Li, Mengjiao; Sun, Wenwu; Li, Jian; Liu, Leshan; Wang, Yihui; Sun, Silei; Xu, Lili; Qi, Xing; Xie, Mengqi; Zhou, Yuhua; Ni, Tongtian; et al. (Frontiers in Medicine, 2022)
Background: Sepsis is an inflammatory syndrome with life-threatening organ dysfunction and high mortality. In the recent 10 years, high dose intravenous injection of vitamin C, the first line antioxidant of human, has received highlighted attention in the field of critical care. The aim of this study is to examine the efficacy and safety of high dose intravenous vitamin C on the treatment of sepsis. Methods and Design: Here we conducted a prospective, multi-centered, double-blinded, randomized, placebo-controlled superiority study named HDVCOS. A total of 620 participants diagnosed with sepsis in 4 participating sites across China that satisfy the eligible criteria will be randomized 1:1 to receive treatment with high dose intravenous vitamin C (200mg/kg/24h) or placebo (saline) for 4 days. The primary outcome is 28 days mortality. The secondary outcomes include incidence of organ failure, SOFA sore change, organ support, the relationship between plasma vitamin C concentration and outcomes and adverse events. Conclusion: The findings of this study will provide potential evidence for high dose intravenous vitamin C on the treatment of sepsis. Ethics and Trial registration: The trial protocol has been approved by Clinical Trail Ethics Committee of Ruijin Hospital of Shanghai JiaoTong University School of Medicine (2018-145) and all 5 participating sites. This trial has been registered in Chinese Clinical Trial Registry (ChiCTR1800017633, version 1.3). http://www.chictr.org.cn/showprojen.aspx?proj=29851